Multiparametric ultrasound in thyroid nodules evaluation: risk-stratification (review of literature) - V. A. Solovov; O. N. Ablekova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Ultrasound (US) is the first imaging modality for thyroid parenchyma evaluation. In the last decades, the role of ultrasound has been improved with the introduction of new US software, such as contrast-enhanced ultrasound and US-elastography. US-elastography is nowadays recognized as an essential part of the multiparametric ultrasound examination. More controversial is the role of contrast-enhanced ultrasound in thyroid evaluation, due to its high variability in sensitivity and specificity. We have therefore drawn up an updated representation of the current evidence in the literature for thyroid nodule multiparametric ultrasound evaluation with particular regard to US-elastography and contrast-enhanced ultrasound.